The Influence of Perceived Service Quality and Consumer Satisfaction on Repurchase Decisions at Alfamart Minimarket Sisingamangaraja 2 Medan - Zulfahmi Siregar; Abd.Rasyid Syamsuri; Arief Hadian (CV. Inara, 2021)
This study aims to determine whether service quality and customer satisfaction have a positive and significant impact on repurchase decisions at Alfamart Sisingamangaraja 2 Medan. This study was conducted by using quantitative methods with several tests, they are: the classical assumption test, multiple linear regression, hypothesis testing and R2 test. Based on the results of the regression obtained the equation: Y = 0.948 + 0.408 X1 + 0.349 X2. Based on these data, it can be determined that the tcount is 3.62 and it is known that the service quality variable (X1) has a ttable of 1.29 when compared to tcount, the result was 3.26>1.29, so it can be concluded that the service quality variable (X1) positive and significant effect on the repurchase decision variable (Y). The consumer satisfaction variable (X2) has a tcount of 8.78 when compared to ttable, the result was 8.78> 3.62, so it can be concluded that the consumer satisfaction variable (X2) has a positive and significant effect on the repurchase decision variable (Y). Simultaneously, the service quality and customer satisfaction variables have a positive and significant influence on the repurchase decision variable. This means that the hypothesis in this study is accepted, as evidenced by the value of Fcount > Ftable (59.890> 3.09). Service quality and customer satisfaction have an influence on the repurchase decision variable by 55.1%, while the remaining 44.9% was influenced by other variables not examined in this study.